TINJAUAN KETEPATAN KODEFIKASI DIAGNOSIS PENYAKIT HYPERTENSI BERDASARKAN ICD-10-CM PASIEN RAWAT JALAN PERIODE TRIWULAN 1 TAHUN 2023 DI RSUD SITI FATIMAH AZ-ZAHRA PROVINSI SUMATERA SELATAN - Rizky, Tri; Endang Yulinda; Lely Meriaya Sari (Jurnal Kesehatan dan Pembangunan, 2024)
Coding is very important in the prospective financing system which will determine the amount of fees paid to the FKRTL (Advanced Referral Health Facility). Appropriately coded clinical data will be needed for information for the purposes of patient care, research, improving service performance, resource planning and management, as well as to obtain appropriate reimbursement for health services provided. The accuracy of a code is intended for all types of diseases, one of which is hypertension. The purpose of this study was to determine the accuracy and inaccuracy percentage of hypertension diagnosis codes. This type of research uses a quantitative approach with descriptive methods. The sample of this study was the medical record files of outpatients diagnosed with hypertension in the January-March 2023 period, totaling 71 files. From a sample of 71 files in the diagnosis of hypertension, it was found that the inaccuracy of filling in the hypertension diagnosis code was 7 files (10%). While the accuracy of filling is 64 files (90%). From a sample of 71 files in the diagnosis of hypertension, it was found that the inaccuracy of filling in the hypertension diagnosis code was 7 files (10%). While the accuracy of filling is 64 files (90%). Factors that cause inaccuracies in the diagnosis code are doctors who write the wrong diagnosis due to incomplete medical supporting information, such as checking blood pressure. Completeness of medical supporting examination results can be used as information to determine the appropriate diagnosis code. Another factor was the doctor's writing which was difficult to read which made it difficult for officers to input diagnoses into the SIMRS.